If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-52=-2(a+1)+2(7a+5)
We simplify the equation to the form, which is simple to understand
-52=-2(a+1)+2(7a+5)
Reorder the terms in parentheses
-52=+(-2a-2)+2*(7a+5)
Remove unnecessary parentheses
-52=-2a-2+2+*(+7a+5+)
Reorder the terms in parentheses
-52=-2a-2+(+14a+10)
Remove unnecessary parentheses
-52=-2a-2+14a+10
We move all terms containing a to the left and all other terms to the right.
+2a-14a=-2+10+52
We simplify left and right side of the equation.
-12a=+60
We divide both sides of the equation by -12 to get a.
a=-5
| -126=7(-3x+2)+x | | 3x-(2x+3)=-18 | | -126=7(-3+2)+x | | 4x+10=6x-38 | | -7(1-2n)=105 | | 2/3x+0.5x=x+2 | | 5+2(5x-22)= | | (1-x)((2-x)(1-x)-1)-(-1)((x-1)-0)=0 | | -264=8(6x-3) | | 125=6n+5(4n-1) | | 6w/2=6-2w | | 3x-5(2x+1)= | | 3(x-5)=x+1 | | f(x)=5-x^2 | | 9t-2t=0 | | 25=6n+5(4n-1) | | 4y-5y+3y+5y=2500 | | -100=6v-5(6v-4) | | 2x+18=72 | | -100=6v-(6v-4) | | -104=-2(4-6b) | | -6n-4n=-10 | | a+7+a=13 | | 5k+4k=0 | | -21=8-5p+6 | | 4x+18=6x+8 | | 7(2x+7)=4+50 | | (5v+3)(9-v)=0 | | 6(m+3)+8(4m+1)=37(m+1)-5 | | 7r-5(3r-7)=51 | | u/5=17/8 | | .03(6x+3)=2x-5 |